2021
DOI: 10.1177/23814683211039457
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Meaningful Benefit-Risk Tradeoffs to Promote Patient-Focused Drug Development in Prader-Willi Syndrome: A Discrete-Choice Experiment

Abstract: Background. Prader-Willi syndrome (PWS) is a rare neurodevelopmental disorder causing quality of life impairments such as insatiable hunger (hyperphagia) and obesity. We explored caregivers’ willingness to assume treatment risk in exchange for reduced hyperphagia according to a PWS-validated observer-reported outcome measure. Methods. We partnered with PWS patient organizations to develop a discrete-choice experiment exploring caregivers’ benefit-risk tradeoffs for emerging PWS treatments. The treatment benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Our search identified 11 010 unique studies, eight of which met our eligibility criteria (see Figure 1). One study reported on values and preferences of obesity management related to outcomes of benefits and harms specific to interventions, 30 while the other seven explored general attitudes, beliefs, and perceptions around obesity managment. [31][32][33][34][35][36][37]…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search identified 11 010 unique studies, eight of which met our eligibility criteria (see Figure 1). One study reported on values and preferences of obesity management related to outcomes of benefits and harms specific to interventions, 30 while the other seven explored general attitudes, beliefs, and perceptions around obesity managment. [31][32][33][34][35][36][37]…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…The lack of published data highlights the need for rigorous studies including discrete choice experiments that engage children, adolescents, and families with lived experiences of paediatric obesity to elicit their values and preferences related to the estimated benefits and harms for behavioural, psychological, pharmacological, and surgical treatment modalities. 20,30,46,47 As behavioural and psychological treatment is most commonly recommended as first-line management, the lack of studies that examined values and preferences for outcomes related to this treatment modality highlights the need for prioritizing primary studies in this area. [8][9][10] Such studies could also examine how different developmental stages (e.g.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…There is a push to include rare disease communities in the development of care standards to ensure they are realistic and promote treatments and interventions that are worthwhile to patients [8]. Caregiver and patient input can inform patient-centered clinical trials, such as by informing the selection of relevant outcome measures [9][10][11]. Caregiver and patient preference information is also increasingly integrated into regulatory decision making in the USA and internationally [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Other recent work published by members of our group has shown that QALYs generated using the time-tradeoff method (and not derived from the EQ-5D) can also effectively document meaningful differences in specific symptoms of a pediatric rare condition. 10,11 Finally, we are pleased to hear of the success of other measures such as the DMD-QoL, 12 which the comment authors assert are better able to document what matters to the Duchenne community. We would be further interested in understanding how the responsiveness of such measures compares to that of the EQ-5D in Duchenne.…”
mentioning
confidence: 97%
“…Other recent work published by members of our group has shown that QALYs generated using the time-tradeoff method (and not derived from the EQ-5D) can also effectively document meaningful differences in specific symptoms of a pediatric rare condition. 10,11…”
mentioning
confidence: 99%